Penggunaan Program Plaxis Dalam Studi Penelitian Perkuatan Geotextile Pada Kestabilan Lereng Buatan - Yonas Prima; Galih Pribadi (Jurnal Sipil Krisna, 2023)
This analytical study is expected to understand the safety factor value of natural slopes using geotextile reinforcement arising on multiple slopes. The finite element method is the method used in this analytical study. The model pattern is implemented through several possibilities for the height of the soil fill and the length of the geotextile itself. The soil benchmark indicators used are secondary data from the West Bandung district and use the Meyerhof shear angle approach. The Meyerhof shear angle approach is also used for slope stability analysis using geotextile reinforcement using a length of 2.10 meters has a slope safety factor value below 1.35 so referring to Bowles has occurred and the safety factor value using a length of 4.1 meters and 6.1 meters has a slope safety factor value above 1.35 so that landslides rarely occur.